2019
DOI: 10.1039/c8gc03973a
|View full text |Cite
|
Sign up to set email alerts
|

Access to green primary explosives via constructing coordination polymers based on bis-tetrazole oxide and non-lead metals

Abstract: An environmentally friendly method to prepare new-generation green primary explosives with excellent performances has been developed on the basis of a coordination chemistry strategy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
45
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 66 publications
(48 citation statements)
references
References 38 publications
3
45
0
Order By: Relevance
“…Figure 3a is the XRD patterns of base ECP (Co), ECP (Ni), and ECP (Cu). It is found that the XRD patterns of the three ECPs are highly consistent with the ECP (Mn) in literature, especially in their common strongest diffraction peaks, which suggests that these ECPs have homologous structures [25,[28][29]. Figure 3b shows the FTIR spectra of three kinds of base ECPs.…”
Section: Morphological and Compositional Analysissupporting
confidence: 73%
See 1 more Smart Citation
“…Figure 3a is the XRD patterns of base ECP (Co), ECP (Ni), and ECP (Cu). It is found that the XRD patterns of the three ECPs are highly consistent with the ECP (Mn) in literature, especially in their common strongest diffraction peaks, which suggests that these ECPs have homologous structures [25,[28][29]. Figure 3b shows the FTIR spectra of three kinds of base ECPs.…”
Section: Morphological and Compositional Analysissupporting
confidence: 73%
“…The high-energy ligand of ECP that we chose in this study is 5,5'-bistetrazole-1,1'-diol (H 2 BTO) with a nitrogen content of 65 %, which is also the precursor of TKX-50, a famous highenergy ion salt [26][27]. In addition, the ECPs formed by the coordination of H 2 BTO with five kinds of transition metals were systematically studied by Zhang et al as primary explosives, all of which were proved to have the ability of detonation and damage [28]. Therefore, we will further investigate the aluminized potential of these ECPs in this work.…”
Section: Introductionmentioning
confidence: 99%
“…In light of these factors, nitrogen-rich explosives have garnered significant attention as replacements for canonical primary and secondary explosives. [18][19][20] However, a lack of reported structure-property relationships for nitrogen-rich functionalities such as organic azides and nitrogen-containing heterocycles hampers the rational design of new heterocyclic explosives and structural tuning of existing HEMs.…”
Section: Introductionmentioning
confidence: 99%
“…Over the past several years, the study of energetic materials such as propellants, explosives and pyrotechnics, has got numerous attentions from researchers due to its important impact on the military and civil aspects . Among them, primary explosives have been widely used in industrial initiation devices .…”
Section: Introductionmentioning
confidence: 99%